The The Effect of Nutrients (N and P) and Hormone (IAA) Application on the Growth of Cocoa (Theobroma cacao L.) Plagiotrope Cuttings - Rosyady, Muhammad Ghufron; Pramesti, Riska Ayu; Setiyono, Setiyono; Kusbianto, Dwi Erwin; Subroto, Gatot; Savitri, Dyah Ayu; Hariyati, Yuli; Rahman, Rena Yunita; Ibanah, Indah (Newinera Publisher, 2023)
To support the successful propagation of cocoa plagiotrope cuttings, nutrients (N and P) and hormone (IAA) are applied to increase plant growth. The purpose of this research was to determine the effect of the provision of nutrients (N and P) and hormone (IAA) on the growth of cocoa plagiotrope cuttings. The experiment was carried out factorial with the basic pattern of Completely Randomized Design (CRD) and was repetitively replications by three times. The first factor was the dose of urea (N) and SP-36 (P) which consisted of 3 levels, such as P0 (0 g/polybag urea and 0 g/polybag SP-36), P1 (3,5 g/polybag urea and 2,5 g/polybag SP-36), and P2 (7 g/polybag urea and 5 g/polybag SP-36). The second factor was the concentration of IAA which consisted of 5 levels, such as I0 (0 ppm), I1 (50 ppm), I2 (100 ppm), I3 (150 ppm), and I4 (200 ppm). The results showed (1) the interaction between the application of the nutrients (N and P) and hormone (IAA) had no significant effect on all observed variables except the number of leaves, where the best treatment combination was the application of fertilizer doses of 0 g/polybag urea + 0 g/polybag SP-36 and IAA concentration of 100 ppm (P0I2) (2) application of the nutrients (N and P) with dose of P1 increased seedling growth on all observed variables except the number of leaves, shoot diameter, and shoot length (3) application of IAA with concentration of I1 increased seedlings growth, that is the number of primary roots/cuttings and shoot length.